Human balance function diagnostic and improvement model within social telerehabilitation system - Gorbunovs, Aleksandrs; Kapenieks, Atis; Lubkina, Velta (Social Welfare: Interdisciplinary Approach, 2017)
Very often persons with disabilities are faced with several obstacles such as lower level of services, limitations and inadequate access to education, health care, information and communication technology resources, unsuitable buildings entrance and workplaces equipment. Existing e-health models are rather general. The aim of this paper is to propose new social telerehabilitation system supportive human balance function diagnostic and improvement model which would enhance inclusion process